Comparative Analysis of Conventional Methods with BIM Methods on Construction Cost Estimate at Structure Project Design Calculations (Case Study of Construction of A Satpol PP Building) - Ulinnuha, Nadira Zalfa; Handayani, Fajar Sri; Rifai, Muji (Indonesian Journal Publisher, 2024)
Construction cost estimate in construction projects requires high accuracy in calculating work volumes and applying unit cost analysis. Lack of accuracy in calculating the volume of work can result in inaccurate cost estimates, causing project budget overruns. This research discusses the use of 3D BIM planning concepts using Autodesk Revit software to help calculate volumes accurately, with the aim of reducing project budget overruns. Comparative analysis of cost estimates between the use of Autodesk Revit and conventional methods provides an overview of the efficiency and effectiveness of using BIM software in estimating construction project costs. The object of this research is the Satpol PP Bantul office construction project, with a focus on structural work. This research method includes data collection, 3D BIM modeling, calculating cost estimates based on the volume produced using unit cost analysis, and comparative analysis of cost estimates between the use of BIM software and conventional methods. Based on the research results, it found that the construction cost estimate for structural work from Revit had a value of IDR 862,330,518.59 and a difference of IDR 53,420,195.31. This shows that the use of the 3D BIM concept results in 5.83% cheaper calculations than conventional construction cost estimate methods.